1999
DOI: 10.1016/s0893-133x(99)00015-9
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone in the Prevention of the Adverse Cognitive Effects of ECT A Within-Subject, Placebo Controlled Study

Abstract: Electroconvulsive therapy (ECT) is a highly effective treatment for major depression, but is also associated with characteristic cognitive side effects. Several reports document that endogenous opioids and their receptors are activated by electroconvulsive shock (ECS) and that naloxone in doses sufficient to block endogenous opioid receptors may reverse ECS-induced retrograde amnesia. This placebo-controlled, randomized, within-patient study was conducted to examine the potential of naloxone, given in doses su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 64 publications
0
14
0
5
Order By: Relevance
“…2017; 19 (9):e59814. 5 tained results showed that high dose of naloxone is fruitless in retrograde memory tests, even leaving a negative trace in "shape stimuli" test evaluation (17).…”
Section: Mind Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…2017; 19 (9):e59814. 5 tained results showed that high dose of naloxone is fruitless in retrograde memory tests, even leaving a negative trace in "shape stimuli" test evaluation (17).…”
Section: Mind Controlmentioning
confidence: 99%
“…Ability of naloxone as an opioid receptor antagonist has been discussed in animal studies (23,24). Also, human studies based on the ability of naloxone have been leading to paradoxical results (17,25).…”
Section: Mind Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Like piracetam, studies demonstrated inconsistent results. One study failed to show a significant effect [13], while in another later study, naloxone improved anterograde amnesia after ECT, but seemed to worsen retrograde amnesia [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mit der Anwendung des NMDA-Antagonisten Ketamin als Anästhetikum anstatt der üblichen kurzwirksamen Barbiturate könnte man selektiv und damit protektiv in diesen Mechanismus eingreifen [61]. Klinisch geprüft wurde die Anwendung von Naltrexon [62]. Verabreichte man Naltrexon in ausreichender Dosierung zur Blockierung der Opioidrezeptoren, beobachtete man klinisch eine deutliche Besserung der anterograden Amnesie sowie der Aufmerksamkeitsleistung im direkten Vergleich zu Placebo und niedrigen Dosen von Naltrexon.…”
Section: Prävention Und Therapie Von Kognitiven Störungen (S Tab 3)unclassified